Environmental aspects of anthropogenic development of Altai mountain areas - Korf Ekaterina D. (E3S Web of Conferences, 2023)
The difficulties in finding a balance in the relationship between recreational activities and geosystems are considered. At present there are geoecological problems in mountainous areas of Altai, connected with intensively increasing anthropogenic load on vulnerable landscapes, some elements of geodiversity and territories of remote areas of the Altai Republic. The importance of nature protection and educational function of "Altai" Geopark in protecting the unique elements of geodiversity from human activity is indicated, and in general, the role of "Altai" Geopark and the importance of giving it UNESCO status in further development of ecological and moral tourism in Kosh-Agach region. The issues of overuse of monuments of inanimate nature as objects of excursion show in the context of increasing anthropogenic pressure on them in connection with the increasing annual tourist flow to Kosh-Agachsky district of the Republic of Altai are considered. The role of the development of the geopark "Altai" and giving it the status of UNESCO in the further development of ecological and moral tourism in Kosh-Agachsky area is considered.